The degree to which second- grade intermediate Students in Riyadh are able to achieve levels of Conceptual comprehension and metacognitive skills from the point of view of Islamic studies course Teachers - Al-Khaldy, Haya Hatem (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to specify to what extent second intermediate grade students in Riyadh city were able to master conceptual conceivableness and metacognition skills from Islamic Studies Courses' teachers. In order to achieve this objective, the descriptive method was used, and the survey was the basic study tool. The study population included all Islamic Studies teachers in Riyadh with no. (1404 teachers). The study sample was selected using simple random sampling method and it included (308 teachers). The results showed that the participants are neutral in their attitude toward second intermediate grade students' mastering of conceptual conceivableness from their viewpoint. In fact, explanation domain was in the first rand followed by application domain, then interpretation domain, emotional sharing, following a perspective, finally there is self- knowledge with neutral degree for all domains expect explanation domain with agree degree.Besides, the results indicated that the participants are neutral in their attitude toward the degree of second intermediate grade students' mastering of metacognition skills whereas planning skill was in the first place with agree grade, followed by supervision skill with neutral degree, however, the evaluation skill was in the final place with neutral degree. In terms of these results, the study recommended the necessity of developing metacognition skills in curriculums and Islamic studies course in order to develop students' conceptual conceivableness levels.
Keywords: conceptual conceivableness; metacognition skills; intermediate stage